Genetic and environmental factors in skin color determination - Callixte Yadufashije* and Rebero Samuel (African Journal of Biological Sciences, 2019)
The origin of skin color has been significantly a discussion of importance among human biology scientists, anthropologists and others interested in evolution of human skin color. Experience was done to chimpanzee and other primates shared almost the same characters with mankind, and this impressed scientists to know what makes difference in skin color among people. Different researches conducted to know the real cause of dark skin and light skin among people of the same origin. There are no other results found out of permanent variation happened to our ancestors based on geographical location. Environmental factors played a huge role in skin color determination. High UVR has been led to dark skin color and low production of UVR led to lightly skin. By natural selection genes responded to environmental conditions for a human to survive in his own environment. Melanin production came as a response to UVR to protect against consequence of UVR in low latitude regions. Depigmentation happened due migration from low latitude to high latitude regions and led lightly skinned color for our ancestors. Everyone has skin color due to ancestry antique geographical location.
Keywords: Skin color, Environmental factors, Human skin, Melanin, Ancestors